Chiral triclinic metamaterial crystals supporting isotropic acoustical activity and isotropic chiral phonons. (3rd February 2021) - Chen, Yi; Kadic, Muamer; Wegener, Martin
Abstract : Recent work predicted the existence of isotropic chiral phonon dispersion relations of the lowest bands connected to isotropic acoustical activity in cubic crystalline approximants of three-dimensional (3D) chiral icosahedral metamaterial quasi-crystals. While these architectures are fairly broadband and presumably robust against fabrication tolerances due to orientation averaging, they are extremely complex, very hard to manufacture experimentally, and they show effects which are about an order of magnitude smaller compared with those of ordinary highly anisotropic chiral cubic metamaterial crystals. Here, we propose and analyse a chiral triclinic metamaterial crystal exhibiting broadband isotropic acoustical activity. These 3D truss lattices are much less complex and exhibit substantially larger effects than the 3D quasi-crystals at the price of being somewhat more susceptible to fabrication tolerances. This susceptibility originates from the fact that we have tailored the lowest two transverse phonon bands to exhibit an 'accidental' degeneracy in momentum space.